2021
DOI: 10.1096/fj.202002675r
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine gamma‐lyase/H2S signaling facilitates myogenesis under aging and injury condition

Abstract: Hydrogen sulfide (H 2 S) can be endogenously produced and belongs to the class of signaling molecules known as gasotransmitters. Cystathionine gamma-lyase (CSE)-derived H 2 S is implicated in the regulation of cell differentiation and the aging process, but the involvements of the CSE/H 2 S system in myogenesis upon aging and injury have not been explored. In this study, we demonstrated that CSE acts as a major H 2 S-generating enzyme in skeletal muscles and is significantly downregulated in aged skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…3 H). Furthermore, the regions of open chromatin in Bmal1 –/– cells include previously annotated enhancer regions, identified by the presence of H3K27ac ( Blum et al 2012 ), which promote the transcription of genes that facilitate myogenesis in injured muscle (e.g., Cystathionin γ-lyse [ Cth ]) ( Zhang et al 2021 ) or participate in early myogenesis (e.g., Mylk4 ) ( Fig. 3 I; Shang et al 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…3 H). Furthermore, the regions of open chromatin in Bmal1 –/– cells include previously annotated enhancer regions, identified by the presence of H3K27ac ( Blum et al 2012 ), which promote the transcription of genes that facilitate myogenesis in injured muscle (e.g., Cystathionin γ-lyse [ Cth ]) ( Zhang et al 2021 ) or participate in early myogenesis (e.g., Mylk4 ) ( Fig. 3 I; Shang et al 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…Both chronic inflammatory reaction and oxidative stress have been already proposed in the pathogenesis of skeletal muscle atrophy due to different etiologies ( Moylan and Reid, 2007 ; Meng and Yu, 2010 ). Previous studies have shown that administration of H 2 S donor NaHS can alleviate skeletal muscle atrophy induced by type 2 diabetes ( Bitar et al, 2018 ), hyperhomocysteinemia ( Majumder et al, 2018 ), ventilator ( Ichinoseki-Sekine et al, 2021 ), cardiotoxin ( Zhang et al, 2021 ), and denervation ( Kuo et al, 2015 ) by attenuating inflammation, oxidative stress and protein degradation. The present study demonstrated that treatment with either slow (GYY4137) or rapid (NaHS) H 2 S releasing donors protected mice against immobilization-induced muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CBS, 3-MST and CAT are also involved in producing H 2 S [ 27 ]. The CTH/H 2 S system plays a part in both health and diseases, and is implicated in the regulation of multiple physiological and pathological effects, including inflammation, immune response, cell differentiation, cancer, aging and the injury process [ 6 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are widely distributed in mammalian tissues, including the liver, kidney, retina and spleen, and are induced by external stimulation and the intracellular environment [ 15 ]. The CTH/H 2 S system plays a part in both health and diseases, and CTH-derived H 2 S is implicated in the regulation of multiple signal physiological effects, including immune response, cell differentiation, cancer, aging and the injury process [ 6 , 16 ]. In addition, Cys, a non-essential amino acid with a nonpolar sulfhydryl group (-SH), is abundant in milk, and provides many substrates for endogenous H 2 S synthesis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%